A dynamic model combining the average and the local meshing stiffnesses and based on the static transmission error for spur gears with profile modification. (February 2023) - Abruzzo, M.; Beghini, M.; Santus, C.; Presicce, F.
Abstract: A dynamic model that evaluates the working condition of general spur gears based on a two-phase approach is presented. A finite element model is preliminary developed to obtain the static transmission error for several angular configurations at different nominal torques. Subsequently, a lumped parameter model is used to evaluate the dynamic behavior of the transmission. An analytical mesh-force formulation is proposed based on polynomial interpolations of the finite element results to accurately model the contact forces and meshing stiffness during the engagement. Two damping models are implemented to obtain a reasonable estimation of the response peaks in resonance conditions. The stability of the main resonance peaks is examined using Poincaré maps. The results are compared with those obtainable using the commonly employed models based either on the average or the local meshing stiffness, highlighting the limitations of these approaches. The proposed formulation combines classical mesh stiffness definitions, thereby achieving a more accurate and efficient mesh-force model. Highlights: The dynamic behavior of a spur gear pair is investigated using two different models. A novel load and time dependent mesh force model is proposed. The results are obtained for different torques and with different damping models. The results are compared with literature approaches and experimental results. The stability of the resonance peaks of the system is studied using Poincaré maps.